Historical global and regional spatiotemporal patterns in daily temperature - Rahim, Md Adilur; Rohli, Robert V.; Mostafiz, Rubayet Bin; Bushra, Nazla; Friedland, Carol J. (Frontiers in Environmental Science, 2024)
The abrupt increase in surface air temperature over the last few decades has received abundant scholarly and popular attention. However, less attention has focused on the specific nature of the warming spatially and seasonally, using high-resolution modelreanalysis output based on historical temperature observations. This research uses the European Centre for Medium-range Weather Forecasts (ECMWF) Reanalysis Version 5 (ERA5) model output to identify spatiotemporal features of daily mean surface air temperature, defined both as the mean of the maximum and minimum temperatures over the calendar day ("meanmaxmin") and as the mean of the 24 hourly observations per day ("meanhourly"), across the terrestrial Earth. Results suggest temporal warming throughout the year, with several "hot spots" of significantly increasing temperature, including in the Arctic transition seasons, Northern Hemisphere midlatitudes in July, Eurasia in spring, Europe and the lower latitudes in summer, and tropical autumn. Cooling is also observed, but generally at rates more likely to be statistically insignificant than warming rates. These trends are nearly identical regardless of whether calculated as "meanmaxmin" or "meanhourly." These results may assist scientists and citizens to understand more fully observed agricultural, commercial, ecological, economic, and recreational trends in light of climate change considerations.